The role of woodlands in the small ruminant production in northeast Portugal - Castro, Marina (2015)
Small ruminant production is a very extensive activity in the northeast of Portugal, mainly based on use of spontaneous vegetation. Driven by shepherds, goat and sheep flocks use several daily itineraries, crossing over a highly diversified landscape; composed by a mosaic of diverse land uses (Forestlands, scrublands, pastures, and annual and perennial croplands).